Fairy Rings - Monica L. Elliott; Philip F. Harmon (EDIS, 2011)
Fairy rings, especially the mushrooms, are most commonly observed during the summer months, when Florida receives the majority of its rainfall. This revised 2-page fact sheet with identification and control information was written by M. L. Elliott and P. F. Harmon, and published by the UF Department of Plant Pathology, February 2011.